LAPPI: A light‐weight technique to practical process modeling and improvement target identification. Issue 9 (24th September 2012) - Raninen, Anu; Ahonen, Jarmo J.; Sihvonen, Hanna‐Miina; Savolainen, Paula; Beecham, Sarah
ABSTRACT: Understanding the current state of the software processes and their problem points is important. Without this understanding, software process improvement (SPI) resources may be allocated to less meaningful targets. SPI work can be challenging to initiate especially in small companies where resources and knowledge of SPI are often limited. The aim of the developed technique, LAPPI (A Light‐weight Technique to Practical Process Modeling and Improvement Target Identification), is to provide an easy to use, lightweight tool for process modeling and improvement target identification. The technique provides a suitable method that integrates with various SPI initiatives. The method used in the development of LAPPI is a nonformal variation of constructive research. LAPPI has been incrementally developed in multiple academia‐industry collaboration projects and by industry actors themselves. Our evaluation of the LAPPI technique in 42 studies conducted in 31 companies indicates that the technique is suitable for modeling the current process and identifying the points of improvement in the process. Practical experience shows that LAPPI provides a cost‐effective technique for process modeling and improvement target identification especially in small and medium‐sized enterprises. It is most useful in the diagnosing phase of SPI. It helps the company to understand the current processes and the organizational interactions, and to create a process description baseline. Copyright © 2012 John Wiley & Sons, Ltd. Abstract : One of the most important challenges encountered by any software process improvement (SPI) initiative is the lack of resources. The lack of resources manifests itself as the lack of knowledge on SPI and the limited possibility of investing effort to the required activities. These restrictions are severe and results from improvement work are required fast especially in small and medium‐sized enterprises. In this paper, we present one solution to these challenges. The LAPPI (A Light‐weight Technique to Practical Process Modeling and Improvement Target Identification) technique is particularly developed to address and identify problem points in a process. LAPPI has been incrementally developed in academia–industry collaboration over 10 years. In this paper we present the LAPPI technique and 42 modeling cases conducted in 31 companies where LAPPI has been applied.